A visual study on Javanese famous cuisine guide book / Siti Nur Afiqah Mohd. Nahar - Mohd. Nahar, Siti Nur Afiqah (2019)
Malaysia has known by worldwide with its multi-culture society. In Malaysia, there are many Javanese descendants that still live in our society. There is many to discover in Java culture. One of them is their traditional famous cuisine. It helps to show the original Javanese recipes that had been inherited to generation to generation. This study is to focus on Javanese famous cuisine guide book. Reason this topic has been highlight in this research is because most of young Orang Java have either never learned it or cannot remember how to cooked traditional Javanese cuisine. This descriptive study is to gain more information in understanding about Javanese famous cuisine. To make this descriptive study more clearly and understanding about cooking guide book for Javanese cuisine. Guide book can help and guide people on how to cook and prepare a meal. Basically, this descriptive study more clearly and understanding by doing illustration method in order to show the steps on how to cook Javanese famous cuisine. Other than that, from this descriptive study it can help not just for the Javanese descendant but also for the other culture to learn on how to cook Javanese cuisine.